Linking per capita income, renewable energy, natural resources, trade, and Urbanisation to material footprint: insights from Saudi Arabia - James Temitope Dada; Mamdouh Abdulaziz Saleh Al-Faryan (Energy Nexus, 2024)
In view of growing greenhouse gases and climate change, this paper investigates the effect of per capita income, renewable energy, natural resources, trade, and urbanisation on the material footprint of Saudi Arabia. This study uses data from 1990 to 2019. Autoregressive Distributed Lag, Fully Modified Ordinary Least Squares, Dynamic Ordinary Least Squares, and Canonical Cointegrating Regression are used as estimation techniques. The result hints that per capita income, renewable energy, natural resources, trade, and urbanisation are determinants of material footprint in Saudi Arabia. Furthermore, the short- and long-run results show that per capita income, trade, and urbanisation increase material footprint, contributing significantly to Saudi Arabia's ecological damage. However, renewable energy and total natural resources rent reduce the material footprint in both periods. Other cointegration techniques also support the long-run estimates. The implications of the result for a sustainable environment were discussed.